Devotion, worship space and power: The echo of the ‘Theotokos’ in the Basilica of Santa Maria Maggiore (century V) - Campos, Ludimila Caliman (Romanitas - Revista de Estudos Grecolatinos, 2015)
This article aims to analyze the construction of the Basilica of Santa Maria Maggiore, especially the Marian mosaics located on the triumphal arch, in order to grasp the reasons why they were there engendered. In addition, we seek to understand how devotion to Mary was established on site contributing to the legitimacy of the authority of the bishop of Rome, who now represents the emanation of power and divine purposes.